Avaliação da contribuição ambiental e socioeconômica de uma unidade rural de produção de biogás no município de Monteiro – PB - Silva, Emanuelle Maria Cabral Avelino (2017)
The search for technologies adapted to the reality of the rural man located in the semi-arid is one of the current trends, since the insertion of new knowledge contributes to the improvement and efficiency of productive activities in rural properties. Among the several existing technologies, biodigestion of agricultural waste has been an application with important advantages for rural properties. In addition to entering an environmental contribution to the treatment of waste, biogas digesters provide, which can be used as a fuel source, and the bio-fertilizer, which is a rich organic fertilizer in replacement of nutrients to the soil. In this context, the present study aims to evaluate the main environmental and socioeconomic contributions of a biogas production system in a rural unit located in the city of Monteiro-PB. The biodigester designed and installed in the property was of the sertanejo type, due to the low cost of construction and maintenance. The same was designed for an energy capacity equivalent to 7 cookware per month, showing to be one of the main socioeconomic contributions. Its structure is composed of a fermenter of 16 m³ and a gasometer of 5 m³. In order to evaluate the available biomass, experiments were carried out in the laboratory, in order to characterize and evaluate the biogas production. The organic matter reduction was verified using the COD (Chemical Oxygen Demand) parameter. Three types of biomass samples were evaluated, such samples being pure swine manure and bovine, and the third with 50% each, or 1: 1. With monitoring of 45 days of digestion, the best biogas production results were of the 1: 1 mixture, with COD reduction of 69%. In turn, the main environmental contribution of the biodigester in the property is the use of a sanitary barrier in the pig farm, where waste is treated, reducing the presence of vectors and disease transmitters.